Pelatihan dan Penguatan Enterpreneurship Building pada Wirausahawan Muda MA Sunan Gunung Jati Pasuruan - Fauzi, M. Asif Nur; Nuruddin, Nuruddin; Holili, Mukhamad; Machrus, Ali (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The problems of low entrepreneurial literacy, minimal business experience, and the dominant orientation of students as job seekers are the main challenges in fostering an entrepreneurial spirit among the younger generation. This condition is also found in young entrepreneurs at MA Sunan Gunung Jati Pasuruan, who have great potential but have not been supported by systematic strengthening of entrepreneurial competencies and mentality. This community service activity aims to provide training and strengthening entrepreneurship building to improve students' entrepreneurial knowledge, attitudes, and skills. The implementation method includes participatory training, providing entrepreneurship materials, business motivation, group discussions, and practical preparation of simple business plans based on local potential and Islamic values. The results of the activity showed an increase in participants' understanding of the concept of entrepreneurship, growing self-confidence, independence, and courage in seizing business opportunities. In addition, participants were able to identify realistic business ideas and have an ethical orientation and social responsibility. This activity makes a real contribution to developing young entrepreneurs with character, adaptability, and competitiveness.